Safety and Probiotic Evaluation of Lactiplantibacillus plantarum CHEN1 and Its Metabolic Analysis of Soymilk Oligosaccharides - Zhina CHEN; Shiyi CAO; Linlin YIN; Mengyuan SHAO; Tao YE; Zhangrui XU; Xiaochen HUANG (Shipin gongye ke-ji)
Lactiplantibacillus plantarum was an important source of probiotics. To evaluate the safety, probiotic properties, and metabolic potential of carbohydrate-active enzymes of L. plantarum CHEN1. The genetic characteristics of the strain were analyzed through genome sequencing and functional annotation. Phenotypic experiments, including hemolytic activity assays, detection of harmful metabolites, antibiotic susceptibility testing, tolerance experiments, hydrophobicity, and autoaggregation assays were conducted to evaluate its safety and probiotic potential. Furthermore, its metabolic mechanism for soymilk oligosaccharides was elucidated. The results showed that the strain's genome lacked genes associated with harmful metabolism, such as nitroreductase and trypsin. Hemolysis tests and harmful metabolite detection were negative. Antibiotic susceptibility testing showed sensitivity to β-lactam and chloramphenicol antibiotics, with low transferability of resistance genes, indicating high safety. The strain exhibited a survival rate of 22.47% after incubation at pH2.0 for 2 h, 33.80% in 0.3% bile salts, and 73.32% in simulated gastrointestinal fluid. The hydrophobicity and autoaggregation rates were 41.83% and 13.47%, respectively, demonstrating good probiotic characteristics. Genome functional annotation revealed that the strain possessed complete metabolic pathways for raffinose and stachyose, which were validated through soymilk fermentation experiments. After fermentation, the stachyose content in soymilk decreased from 1043.83 mg/L to 536.01 mg/L, and the raffinose content decreased from 270.69 mg/L to 134.69 mg/L, indicating that CHEN1 had a strong metabolic capacity for these two sugars and the potential to degrade flatulence-inducing factors in soymilk and improve digestibility. In conclusion, L. plantarum CHEN1 exhibits potential safety and probiotic properties and can be used as a functional strain for the fermentation of plant-based foods.